Comparison of Oxidative Stress in Neonates Born by Normal Vaginal and Elective Caesarean Delivery - Tanvi Pai; Rajesh Shimoga Mahabala; Shantharam Baliga (JCDR Research and Publications Pvt. Ltd., 2017)
Introduction: Oxidative stress occurs when generation of free radicals (oxidants) exceeds the available antioxidants. In pregnancy and parturition, there is an increased formation of reactive oxygen species. This study aims to evaluate and compare oxidative stress in newborns delivered by two different modes i.e., normal Vaginal Delivery (VD) and elective Caesarean Section (CS). Aim: To evaluate and compare oxidative stress in term new born via two different modes of delivery i.e. Normal VD and elective CS by estimating the following serum biochemical markers in a cord blood sample. 1) Superoxide Dismutase (SOD) 2) Uric Acid (UA) 3) Malondialdehyde (MDA) 4) Ischemia Modified Albumin (IMA). Materials and Methods: A hospital based cross-sectional study was conducted wherein a total 92 neonates, 46 in each group of normal VD and elective CS were included in the study. Cord blood levels of oxidative stress parameters i.e., MDA, IMA and antioxidants - SOD and UA were estimated. Statistical analysis of the outcome variables was done by Chi square, Fischer Exact, unpaired 't'-tests and ANOVA. Correlation between parameters by Pearson's correlation and significant parameters were subjected to ROC curve analysis to see their efficacy. Results: The IMA levels in cord blood were significantly higher in VD (p<0.05) when compared to CS, while MDA levels were not significantly different between the groups (p>0.05). The levels of antioxidant parameters SOD and UA was significantly lower in neonates born by VD than CS (p<0.05). IMA showed a significant weak positive correlation with the period of gestation. The area under ROC of IMA was 0.985 showed significant difference between both groups. Conclusion: There is increased oxidative stress and decreased antioxidant status in neonates born via normal VD as compared to CS. There is decreased oxidative stress during caesarean delivery as depicted by decreased IMA and higher antioxidant reserve (SOD and UA) in the cord blood these babies which in turn is a protective mechanism. The negative correlation between the oxidative parameter (IMA) and antioxidant parameters (SOD, UA) can be explained by the free radical scavenging effect of antioxidants which is reflected with comparatively lower levels.